1982
DOI: 10.1095/biolreprod26.4.765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porcine Relaxin on Cervical Dilatation, Pelvic Area and Parturition in Beef Heifers1

Abstract: Purified porcine relaxin (3,000 U/mg) was administered either into the cervical os or by intra-muscular injection to crossbred beef heifers beginning 4 days before expected parturition, in an attempt to elucidate the physiological roles of relaxin in cervical dilatation, the pelvic area, and parturition. Relaxin (3,000 U in a gel vehicle), when administered into the cervical os during late pregnancy, induced significant dilatation of the cervix 8 and 16 h later, as compared to vehicle-treated controls. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Pelvic area increases gradually in cattle throughout gestation, then the rate increases during the last 4 days preceding normal parturition, which coincides with increasing blood concentrations of 17/3-estradiol (17jS-E 2 ) and estrone (Ei) (15)(16)(17)(18)(19)(20). Administration of porcine relaxin increases both pelvic area and cervical dilatation in beef heifers during late pregnancy (21,22). The objectives of this study were to determine the effects of intracervical administration of purified porcine relaxin during late gestation in cattle on the induction of parturition, cervical dilatation, and pelvic relaxation as well as plasma concentrations of Ei, 17jft-E 2 , and progesterone.…”
mentioning
confidence: 98%
“…Pelvic area increases gradually in cattle throughout gestation, then the rate increases during the last 4 days preceding normal parturition, which coincides with increasing blood concentrations of 17/3-estradiol (17jS-E 2 ) and estrone (Ei) (15)(16)(17)(18)(19)(20). Administration of porcine relaxin increases both pelvic area and cervical dilatation in beef heifers during late pregnancy (21,22). The objectives of this study were to determine the effects of intracervical administration of purified porcine relaxin during late gestation in cattle on the induction of parturition, cervical dilatation, and pelvic relaxation as well as plasma concentrations of Ei, 17jft-E 2 , and progesterone.…”
mentioning
confidence: 98%
“…Studies conducted to examine the effects of highly purified relaxin in pregnant animals have shown that relaxin stimulates growth and softening of the cervix in pigs and rats (Downing and Sherwood, 1985). Similar properties of relaxin were observed in cattle (Perezgrovas and Anderson, 1982;Musah et al, 1988), in these studies relaxin administration during late pregnancy promoted increased pelvic area and facilitated earlier calving in treated animals compared with untreated controls. reported that relaxin has growth-promoting properties on the cervix during late pregnancy.…”
Section: Reproductive Tract Changes During Pregnancy and Parturitionsupporting
confidence: 80%
“…Moreover, RLX induced suppression of OT release from corpus luteum in cow [28]. Bovine corpora lutea from late pregnancy contain active RLX, while there is markedly lower than in swine [29]. Since it was found previously that PCBs increased amount of stimulators of contractions (OT and PGF2), here it was hypothesized that PCBs can increase the uterine The aim of this study was to investigate the effect of PCB 77 and PCB 153 on myometrial reception of RLX signal during pregnancy, and therefore on (a) mRNA expression of receptor of RLX and (b) RLX-inhibition of myometrial strips contractions.…”
mentioning
confidence: 93%
“…While to study the inhibition of contractions, there were used two type of RLX. It was porcine RLX (30, 60 and 100 ng/ml, according to Kaczmarek et al [32], it is 200-500 ng/ml) since it was also used in study in beef heifers in vivo [29,33]. Since signaling by Relaxin-2 human through its target receptors enhances the growth of pubic ligaments and ripening of the cervix during birth [34] it was also used in this study (10-400 ng/ ml).…”
mentioning
confidence: 99%